Biomechanics and biocompatibility assessment of bone drilling for surgical application: asystematic literature review - Lenggo Ginta, Turnad Lenggo Ginta; Mujiarto, Mujiarto; Jufriadi, Jufriadi; Setyobudi, Nanang; Yulianto, Katri; Febriansyah, Dwi Jaya; Azka, Muizuddin (Politeknik Negeri Lhokseumawe, 2024)
This systematic literature review delves into the intricate relationship between biomechanics and biocompatibility within the context of bone drilling for surgical applications. It meticulously analyzes the forces, stresses, and strains that bone undergoes during drilling, shedding light on essential variables crucial for enhancing surgical efficacy. Moreover, it scrutinizes the mechanical attributes of drilling tools, particularly drill bits, assessing factors such as material composition, design intricacies, and heat generation, all of which profoundly influence drilling performance. The review also thoroughly investigates the implications of drilling materials on bone tissue biocompatibility, addressing concerns such as corrosion, wear debris, and potential toxicity. By synthesizing current research, it offers up-to-date insights into advancements and strategies aimed at overcoming challenges in bone drilling. Ultimately, this review serves to refine bone drilling techniques, advocating for safer and more efficient surgical practices, and ultimately aiming to improve patient outcomes through a comprehensive understanding of biomechanical and biocompatibility considerations.